Loss of production and animal health costs in assessing economic burden of animal disease. - Marsh TL; Pendell D; Schrobback P; Shakil G; Tozer P (World Organisation for Animal Health, 2024)
This article focuses on identifying the loss of production and costs (or lack thereof) associated with livestock health as well as animal disease externalities, with the intent to estimate economy-wide burden. It limits its scope to terrestrial livestock and aquaculture, wherein economic burden is predominately determined by market forces. Losses and costs are delineated into both direct losses and costs and indirect losses and costs, as well as ex post costs and ex ante costs. These costs include not only private expenditures but also public expenditures related to the prevention of, treatment of, and response to livestock disease. This distinction is important because a primary role of government is to mitigate externalities. The article then discusses market impacts and investments. Finally, it provides selected examples and illustrative observations and discusses future directions for research and application. Cet article examine les pertes de production et les coûts associés (ou non) à la santé animale ainsi que les externalités liées aux maladies animales, dans le but d’estimer le fardeau pour l’ensemble de l’économie. L’examen se limite à la production d’animaux terrestres et aquatiques, secteurs où le fardeau économique est principalement déterminé par les forces du marché. Les pertes et les coûts sont répartis en pertes et coûts directs et indirects, ainsi qu’en coûts ex post et ex ante. Ces coûts comprennent non seulement les dépenses privées, mais aussi les dépenses publiques liées à la prévention, au traitement et aux réponses aux maladies des animaux d’élevage. Il s’agit d’une distinction importante car l’une des fonctions premières d’un gouvernement est d’atténuer les externalités. Les auteurs examinent ensuite les impacts sur les marchés et les investissements. Pour conclure, à partir d’exemples choisis et d’observations illustrant leur propos, les auteurs proposent des voies d’exploration pour la recherche et ses applications.
Keywords: Animal; Burden; Costs; Diseases; Expenditures; Externalities; Health; Human; Losses; Markets; Animals; Animal Diseases; Cost of Illness; Livestock; Animal Husbandry